Physiological responses of fen mosses along a nitrogen gradient point to competition restricting their fundamental niches. Issue 2 (17th October 2022) - Jaszczuk, Izabela; Kotowski, Wiktor; Kozub, Łukasz; Kreyling, Jürgen; Jabłońska, Ewa
Abstract : Nutrient availability determines vegetation patterns and ecological functioning of intact groundwater‐fed peatlands (fens). Bryophytes, commonly referred to as 'brown mosses', dominate calcareous fens (rich fens), are an integral part of their unique biodiversity and contribute significantly to peat formation and carbon sequestration. Brown mosses are replaced by vascular plants as nutrient availability increases. The decline of brown mosses may either be due to their physiological intolerance of high nutrient levels or to them being outcompeted by vascular plants. We aimed to distinguish between these two hypotheses by investigating whether the ecological optima reflect the physiological optima of brown mosses. Eight brown moss species, common in calcareous fens of the northern hemisphere, were grown under a gradient of nitrogen and phosphorus availability. Biomass increment, chlorophyll content and biomass nutrient concentration were measured. All brown moss species studied achieved the highest growth rates and chlorophyll contents when grown under conditions of nitrogen and phosphorus concentrations higher than those where they occur naturally at the highest frequency. Two of the species showed no growth saturation even at the highest levels of nutrient availability, while the others appeared potassium‐limited at the highest N and P levels. Brown mosses dominate natural fens at the lower edge of their physiological optimum in terms of nutrient availability, i.e. their realized niche is much narrower than the fundamental one. Based on the literature, we argue that it is the competition for light with vascular plants which limits the occurrence of brown mosses in nutrient‐rich habitats and prevents them from occupying their entire fundamental niche.